2011
DOI: 10.1016/j.ydbio.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors AP-2β and AP-2α are required for survival of sympathetic progenitors and differentiated sympathetic neurons

Abstract: Differentiation of sympathetic neurons is controlled by a group of transcription factors, including Phox2b, Ascl1, Hand2 and Gata3, induced by bone morphogenetic proteins (BMPs) in progenitors located in ganglion primordia at the dorsal aorta. Here, we address the function of the transcription factors AP-2β and AP-2α, expressed in migrating neural crest cells (NCC) and maintained in sympathetic progenitors and differentiated neurons. The elimination of both AP-2α and AP-2β results in the virtually complete abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 63 publications
7
57
0
Order By: Relevance
“…In mice the transcription factor TFAP2B is known to regulate noradrenaline signaling (Hong et al 2008;Schmidt et al 2011), and in Drosophila TFAP2B is encoded by the homolog TfAP-2 (Monge et al 2001). Since octopamine, the Drosophila analog of noradrenaline, is known to control aggression and mating behavior in males, we first wanted to determine if TfAP-2 was expressed in octopaminergic neurons.…”
Section: Tfap-2 Is Expressed In Octopaminergic Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice the transcription factor TFAP2B is known to regulate noradrenaline signaling (Hong et al 2008;Schmidt et al 2011), and in Drosophila TFAP2B is encoded by the homolog TfAP-2 (Monge et al 2001). Since octopamine, the Drosophila analog of noradrenaline, is known to control aggression and mating behavior in males, we first wanted to determine if TfAP-2 was expressed in octopaminergic neurons.…”
Section: Tfap-2 Is Expressed In Octopaminergic Neuronsmentioning
confidence: 99%
“…TFAP2B is a member of the AP-2 family of transcription factors, key regulators of various developmental processes (Eckert et al 2005;Meng et al 2010;Wenke and Bosserhoff 2010), and in mice it was demonstrated that TFAP2B is necessary for the proper development of peripheral and central nervous system noradrenergic neurons (Hong et al 2008;Schmidt et al 2011). KCTD15 belongs to a family of potassium-channel tetramerization domain-containing proteins.…”
mentioning
confidence: 99%
“…However, it has not yet been possible to examine the consequence of removing all three Tfap2 paralogs in melanocytes due to another example of redundancy, the lack of neural crest in zebrafish depleted of both Tfap2a and Tfap2c [33,34]. This is also true in mouse, where Tfap2a and Tfap2b are expressed in early neural crest [35] as well as the melanocyte lineage, resulting in almost complete loss of migrating trunk neural crest prior to specification of the melanocyte lineage in Tfap2a/Tfap2b double mutants [36]. Thus, the specific contributions of these factors to the GRN governing melanocyte differentiation have not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Among the AP2 factors, AP2α, AP2β and AP2γ are reported to be the key regulators in neural crest development [25][26][27][28], which is generally thought to occur following the neural plate formation. Conditional disruption of Smad4 in neural crest cells results in AP2α downregulation from embryonic day 9.5 (E9.5) in mouse embryo [29].…”
Section: Introductionmentioning
confidence: 99%